Driving force : the natural magic of magnets - Livingston, James D., 1930- (Cambridge, Mass. : Harvard University Press, 1996)
Scientific discussion of magnets for high school through adult readers, looking at the history of the natural phenomenon and investigating some of the ways magnets are being used today in the fields of science, medicine, technology, and entertainment.
Includes bibliographical references (p. 285-298) and index.
Booklist.
Library Journal Starred.
Wilson's Public Library.
Adult
Keywords: Magnets; Magnets -- Industrial applications; Magnets; Magnets -- Industrial applications